Combustion analysis of modified inverted "M" type piston for diesel engine with platinum coating and without coating by using CFD. (2017) - Yerrennagoudaru, Hiregoudar; Manjunatha, K.
Abstract: In this present work, "COMBUSTION ANALYSIS OF MODIFIED INVERTED "M" PISTON DIESEL ENGINE WITH PLATINUM COATING AND WITHOUT COATING BY USING CFD" is presented. Understanding the nature of the flows and combustion in internal combustion engines are important for improving engine performance. The flows in IC engines can be characterized by swirl, tumble and compression in the cylinder. This flow motion has a strong influence on the engine combustion process and hence on the engine emission of pollutants. Recently simulation results by Computational Fluid Dynamics codes are used in the development and optimization of new engines by car manufacturers (automotive industry). The in-cylinder fluid motion in internal combustion engines is one of the most important factors controlling the combustion process. Swirl and tumble are well known approaches for in-cylinder flow enhancement. Swirl and tumble are generated in the intake stroke as a result of the inlet port shape and orientations.